Molecules to Ecosystems: Actinomycete Natural Products In situ - Behie, Scott W.; Bonet, Bailey; Zacharia, Vineetha M.; McClung, Dylan J.; Traxler, Matthew F. (Frontiers in Microbiology, 2017)
Actinomycetes, filamentous actinobacteria found in numerous ecosystems around the globe, produce a wide range of clinically useful natural products (NP). In natural environments, actinomycetes live in dynamic communities where environmental cues and ecological interactions likely influence NP biosynthesis. Our current understating of these cues, and the ecological roles of NP, is in its infancy. We postulate that understanding the ecological context in which actinomycete metabolites are made is fundamental to advancing the discovery of novel NP. In this review we explore the ecological relevance of actinomycetes and their secondary metabolites from varying ecosystems, and suggest that investigating the ecology of actinomycete interactions warrants particular attention with respect to metabolite discovery. Furthermore, we focus on the chemical ecology and in situ analysis of actinomycete NP and consider the implications for NP biosynthesis at ecosystem scales.